Preparation and application of core-shell structure carbon-coated copper nano antibacterial agent with slow release function

Core-shell structure carbon-encapsulated copper nanoantibiotic agent prepared by plasma arc method solves the problems of easy oxidation and poor stability of nanocopper, and achieves efficient and safe antibacterial effects, especially with significant bactericidal effect on drug-resistant bacteria at low concentrations. ability.

CN119304180APending Publication Date: 2025-01-14INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411413886.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing nanocopper antibacterial agents are prone to oxidation, have poor stability, low biosafety during use, and are prone to sudden release and rapid degradation, reducing the utilization and safety of the material.

Method used

The carbon-covered copper nanoantibiotic agent with core-shell structure is prepared by plasma arc method. Cu@C nanoparticles with spherical structure are formed by pure copper as the core and porous carbon as the shell. The carbon shell is used to protect the copper particles from oxidation and pass carbon. The burning process of the shell adjusts the thickness and particle size distribution of the shell to achieve sustained release of copper.

Benefits of technology

It improves the stability and biosafety of nanocopper, maintains high activity, achieves high-efficiency broad-spectrum bactericidal at low concentrations, avoids drug-resistant bacteria infection, and has good biocompatibility and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119304180A_ABST
    Figure CN119304180A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a core-shell structure carbon-coated copper nano-antibacterial agent with a slow release function, and relates to the technical field of antibacterial nano-metal materials, and the preparation method comprises the following steps: preparing by using a plasma arc method, taking pure copper as an anode, selecting a graphite rod as a cathode, and after the vacuum degree of an electric arc furnace reaches 10 <-4 > Pa or above, carrying out ultrasonic treatment; the method comprises the following steps: injecting a carbon source into a high-vacuum cavity, purifying in argon, collecting black powder consisting of nano-particles, carrying out a carbon shell burning process on the collected nano-particles, cooling, and recovering. The prepared carbon-coated copper nano-particles are of a core-shell structure with copper as a core and porous carbon as a shell, the porous carbon shell protects the nano-copper particles from being oxidized easily, the high activity of the nano-copper is kept, the nano-copper can achieve efficient and broad-spectrum sterilization at low concentration, meanwhile, slow release of the copper is achieved, and it is guaranteed that the antibacterial agent is higher in biological safety and environment friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibacterial nano metal materials, and in particular to the preparation and application of a core-shell carbon-coated copper nano antibacterial agent with a sustained-release function. Background Art

[0002] Bacterial contamination has long been an industry pain point in many fields such as medicine and food. The widespread use of chemical fungicides has caused serious bacterial resistance problems, resulting in increasingly serious secondary bacterial infection problems, posing a serious threat to human health and environmental hygiene. Compared with traditional physical and chemical antibacterial strategies, common antibacterial metal elements such as copper (Cu) and silver (Ag) can destroy cell walls, cell membranes or damage proteins and nucleic acids by producing reactive oxygen species (ROS) to achieve sterilization, so they have broad-spectrum antibacterial properties while avoiding drug resistance problems. In particular, by combining the nano-strategy, the particle size can be fully reduced by nano-preparing the antibacterial metal, and the resulting high specific surface area makes the active sites of the material better dispersed, thereby having stronger biological activity. In particular, copper nano-preparation is inexpensive and simple in composition, and is widely used in the antibacterial field.

[0003] There are many methods for preparing nano copper at present. Rearrangement of atoms by chemical reaction is usually a common method for preparing nano particles. For example, polymers, oleic acid, polyethylene glycol, hydrazine hydrate, etc. containing benzene ring structure are used as reducing agents to react (patent CN101264526A, CN101607317A), and various ketone compounds are used as organic solvents (patent CN108971913A). The use of these organic substances causes difficulty in purifying nano copper, and the residue treatment is complicated and the cost is high. There are also useful plants such as honeysuckle as reducing agents to prepare nano copper (patent CN116329566A, CN1600104A), but due to the uncontrollable stability of the effective ingredients used for reduction in plants, the size, uniformity and stability of the synthesized nano materials are poor. The physical method for preparing nano particles mainly involves physical changes such as evaporation, melting, and solidification. Compared with chemical synthesis, it is not easy to introduce impurity components and does not involve purification post-processing processes. The synthesized nano materials are relatively stable and easy to operate, and have the potential for batch production.

[0004] Nevertheless, the currently synthesized nano-copper mostly involves the individual nano-sizing of copper, which makes the element fully exposed, thereby accelerating the oxidation of copper and affecting the stability of the material. At the same time, in the process of nano-copper exerting its functionality, it will show hidden dangers such as sudden release, rapid degradation and off-target effects, which greatly reduces the utilization and biosafety of the material. Therefore, improving the stability and safety of nano-copper antibacterial agents is a key issue in solving their application in the antibacterial field.

[0005] The preparation of coating on the surface of nano copper is a key technology to improve its oxidation resistance and safety. Especially with carbon coating, it can not only improve the biocompatibility of materials but also overcome the disadvantage of easy agglomeration of nano copper. At present, carbon-coated copper nanoparticles are prepared by alkane reflux method, but the operation processes including material preparation, multiple reflux, etc. are complicated, the preparation process is long, and the preparation process includes the participation of multiple compounds, and the purity of material preparation is difficult to control (patent CN102717070A). In addition, in the existing prepared carbon-coated copper, the carbon coating layer is a closed structure, which leads to limited functionality of copper. Summary of the invention

[0006] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a preparation method and application of a core-shell structured carbon-coated copper nano-antibacterial agent with a sustained-release function. The preparation method of the carbon-coated copper nano-antibacterial agent disclosed in the present invention is simple, has high stability, good biosafety, and excellent antibacterial performance, especially has a good clearing effect on bacterial infections caused by drug-resistant bacteria.

[0007] To achieve the above object, the first aspect of the present invention provides a method for preparing a core-shell carbon-coated copper nano-antibacterial agent with a sustained-release function, comprising the following steps: preparing the agent using a plasma arc method, using pure copper as an anode and selecting a graphite rod as a cathode. -4 Pa or more, the carbon source is injected into a high vacuum chamber. After purification in argon for 12 hours, a black powder consisting of nanoparticles is collected. The collected nanoparticles are subjected to a carbon shell burning process, and then recovered after cooling to obtain Cu@C.

[0008] Furthermore, the carbon source is an organic compound composed of three elements, carbon, hydrogen and oxygen, or two elements, carbon and hydrogen. Anhydrous ethanol (C2H5OH) and n-hexane (C6H 14 ).

[0009] Furthermore, the Cu@C is a core-shell structure with copper as the core and porous carbon as the shell. The porous carbon shell protects the nano copper particles from being easily oxidized, maintains the high activity of nano copper, and enables it to achieve high efficiency and broad-spectrum sterilization at low concentrations. At the same time, the slow release of copper is achieved, ensuring that the antibacterial agent is more biosafe and environmentally friendly.

[0010] Furthermore, the Cu@C has a spherical structure, a porous structure, a uniform size, and a particle size distribution between 30 and 100 nm.

[0011] Furthermore, the carbon source is different, and the thickness of the Cu@C shell is adjustable. When the carbon source is anhydrous ethanol, the particle size of the prepared carbon-coated copper nanoparticles is distributed between 30 and 60 nm, and the thickness of the carbon shell is between 8 and 10 nm; when the carbon source is cyclohexane, the particle size of the prepared carbon-coated copper nanoparticles is distributed between 30 and 60 nm, and the thickness of the carbon shell is between 10 and 19 nm.

[0012] Furthermore, the carbon shell burning process temperature is 150-250°C.

[0013] Furthermore, the carbon shell burning process has a heat preservation time of 0.5 to 3.0 hours.

[0014] Furthermore, the carbon-coated copper nano-antibacterial agent can slowly release copper element.

[0015] Furthermore, the carbon-coated copper nano-antibacterial agent can kill Gram-positive bacteria, Gram-negative bacteria and fungi.

[0016] The second aspect of the present invention provides the use of the carbon-coated copper nano-antibacterial agent. The carbon-coated copper nano-antibacterial agent prepared by the present invention is used in the preparation of drugs and / or bactericides for treating diseases caused by bacteria, and the carbon-coated copper nano-antibacterial agent can slowly release copper to kill bacteria.

[0017] As described above, the preparation and application of the core-shell carbon-coated copper nano-antibacterial agent with sustained release function of the present invention has the following advantages:

[0018] Beneficial effects:

[0019] 1. The core-shell structure carbon-coated copper nano-antibacterial agent provided by the present invention ultimately forms carbon encapsulation of copper to protect the nano-copper particles from being easily oxidized, thereby maintaining the high activity of the nano-copper and achieving efficient sterilization at a low concentration.

[0020] 2. The preparation method of the core-shell structure carbon-coated copper nano-antibacterial agent provided by the present invention utilizes precise shell-breaking technology to make the carbon shell into porous carbon, thereby achieving the sustained release of copper, eliminating the risks of sudden release of traditional pure nano-copper, and being more biosafe and environmentally friendly.

[0021] 3. Compared with traditional antibiotics, the core-shell carbon-coated copper nano-antibacterial agent provided by the present invention utilizes the unique antibacterial mechanism of inorganic metal elements and has a broad-spectrum antibacterial property, especially it can kill resistant Gram-positive bacteria, Gram-negative bacteria and fungi, including methicillin-resistant Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella, etc., but not limited to these, and can also effectively avoid inducing bacterial resistance.

[0022] 4. The core-shell carbon-coated copper nano-antibacterial agent provided by the present invention is prepared by physical method, which has simple operation, stable performance, low cost, high yield, and can be prepared on a large scale. It has great potential for wide application and clinical transformation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Transmission electron micrograph of the synthesized core-shell structured carbon-coated copper nano-antibacterial agent.

[0024] Figure 2 This is the scanning electron microscope image and elemental surface scanning map of the synthesized core-shell structure carbon-coated copper nano-antibacterial agent.

[0025] Figure 3 This is a transmission electron micrograph of the core-shell structured carbon-coated copper nano-antibacterial agent synthesized after changing the carbon source.

[0026] Figure 4 To test the sustained release performance of core-shell carbon-coated copper nano-antibacterial agent.

[0027] Figure 5 The core-shell structure carbon-coated copper nano-antibacterial agent has an antibacterial effect on Gram-negative bacteria, Escherichia coli (ATCC 25922).

[0028] Figure 6 The core-shell structure carbon-coated copper nano-antibacterial agent has an antibacterial effect against drug-resistant Gram-positive bacteria and methicillin-resistant Staphylococcus aureus (ATCC 43300).

[0029] Figure 7 The antibacterial effect of core-shell carbon-coated copper nano-antibacterial agent against Aspergillus niger. DETAILED DESCRIPTION

[0030] The following describes the implementation of the present invention through specific embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0031] Example 1

[0032] This example prepares a core-shell structure carbon-coated copper nanoparticle, and the specific steps are as follows:

[0033] The plasma arc method is used for preparation, pure copper is used as the anode, and graphite rod is selected as the cathode. -4After 100 Pa, anhydrous ethanol was injected into the high vacuum chamber. After purification in argon for 12 hours, a black powder consisting of nanoparticles was collected. The collected nanoparticles were kept at 200 ° C for 1 hour, cooled and recovered to obtain Cu@C.

[0034] Figure 1 3 is a transmission electron microscope image of the core-shell structured carbon-coated copper nanoparticles prepared in this embodiment. The carbon-coated copper nanoparticles are spherical in structure and uniform in size, with a particle size distribution between 30 and 60 nm and a carbon shell thickness between 8 and 10 nm.

[0035] Figure 2 The scanning electron microscope image and elemental surface scanning spectrum of the core-shell structure carbon-coated copper nanoparticles prepared in this example are shown in Figure 1. The spherical nanoparticles are aggregated together and are mainly composed of carbon, copper and a small amount of oxygen, indicating that the prepared nanoparticles are indeed carbon-coated copper.

[0036] Example 2

[0037] According to the preparation method of this Example 1, Cu@C was prepared using n-hexane as a carbon source. Figure 3 The transmission electron microscopy image of the obtained Cu@C nanoparticles is shown in Figure 2. Figure 3 It can be seen that the thickness of the carbon shell is between 10 and 19 nm. Due to different carbon sources, the thickness of the Cu@C shell changes significantly. Because the carbon content of n-hexane is 83.7%, which is much higher than that of anhydrous ethanol (carbon content: 52.2%), the thickness of the Cu@C shell prepared with n-hexane increases. Similarly, by replacing other carbon sources, the thickness of the Cu@C shell can be adjusted.

[0038] Example 3

[0039] In this example, the sustained release performance of the core-shell carbon-coated copper nanoparticles prepared in Example 1 was studied. The specific process was as follows: the core-shell carbon-coated copper nanoparticles were prepared into a 100 μg / mL aqueous solution, which was taken out after being placed for 6 hours, 24 hours, 48 ​​hours, and 72 hours, respectively, and the cumulative release concentration of copper ions in the solution was detected to test the release performance of copper in the core-shell nanoparticles.

[0040] like Figure 4 As shown, the concentration of copper ions in the solution at different time points is detected, and it is clearly shown that the concentration of copper ions increases with time, indicating that the carbon shell of the prepared core-shell structure carbon-coated copper nanoparticles is indeed defectively formed, so that copper ions can be released. As time goes by, the cumulative concentration of copper ions in the solution gradually increases slowly and tends to be stable. Even after standing for 7 days, the total release concentration of copper ions is only 4.36μg / mL, indicating that the core-shell structure carbon-coated copper nanoparticles prepared by the present invention have good sustained release performance.

[0041] Example 4

[0042] This example studies the antibacterial properties of the aqueous solution of the core-shell carbon-coated copper nanoparticles prepared in Example 1. This example uses Gram-negative bacteria Escherichia coli (ATCC 25923) to verify the antibacterial effect of its aqueous solution. The specific process is as follows:

[0043] (1) Inoculate the E. coli strain into LB broth medium and culture it in a 37°C incubator for 8 to 10 hours. Use an ultraviolet spectrophotometer to measure the optical density (OD) at 600 nm. 600 ) is 0.5, the bacteria grow to 10 per ml 8 The bacterial suspension was then diluted to 10 with PBS buffer (0.01 M, pH 7.4). 6 CFU / mL, and the Escherichia coli bacterial suspension for the experiment was obtained, and the bacterial suspension without sample was used as the control group.

[0044] (2) The core-shell structure carbon-coated copper nanoparticles were prepared into suspensions of different concentrations (20, 40, 60, 80 μg / mL) with PBS buffer, and then the bacterial suspensions were mixed with PBS buffer and suspensions of core-shell structure carbon-coated copper nanoparticles of different concentrations in sterile 24-well plates in equal volumes, so that the final concentrations of core-shell structure carbon-coated copper nanoparticles in each mixed system were (10, 20, 30, 40 μg / mL), respectively. After the 24-well plate containing the mixed system was placed in a 37°C shaker for 6 hours, 100 μL of the mixed solution was transferred and evenly applied to the solid culture medium, and the mixture was cultured in a 37°C incubator for 24 hours, and the bacterial colonies on the plate were observed and photographed.

[0045] The implementation results are as follows Figure 5 As shown in the figure, when the final concentration of the core-shell carbon-coated copper nanoparticles is 20μg / mL, it can show significant antibacterial properties compared with the control group. When the final concentration is ≥30μg / mL, the antibacterial rate of the core-shell carbon-coated copper nanoparticles exceeds 99.9%, and it has excellent antibacterial effect on Gram-negative bacteria.

[0046] Example 5

[0047] The difference between this embodiment and embodiment 4 is that the aqueous solution of the core-shell carbon-coated copper nanoparticles prepared in embodiment 1 is used as an antibacterial agent to perform an inhibition effect verification experiment on drug-resistant Gram-positive bacteria (methicillin-resistant Staphylococcus aureus (ATCC 43300)). At the same time, a bacterial suspension without a sample is used as a control group for comparative observation. In addition, in addition to the observation and recording of bacterial colonies as in embodiment 4, the cumulative biomass of bacteria at the bottom of the 24-well plate in the culture system is also detected, and the specific process is as follows:

[0048] According to the detection process in Example 4, 100 μL of the mixed solution in different mixed systems was respectively transferred and evenly applied on the solid culture medium, and the remaining mixed solution in the well plate was discarded. Each well was rinsed 3 times with PBS buffer to remove the floating bacteria and nanoparticles that were not attached to the bottom of the well plate. Then 500 μL of methanol solution was added to each well for fixation for 15 minutes. Then 1 wt.% crystal violet was added to each well to stain the total amount of bacterial biomass attached to the bottom of the well plate. After 15 minutes, the dye was discarded, and the well plate was washed with sterile water and air-dried. Finally, 500 μL of 95% ethanol was added to each well to re-dissolve the bacterial biomass labeled with crystal violet, and the color development was observed and photographed to record the color development.

[0049] like Figure 6 As shown in the figure, when the final concentration of core-shell carbon-coated copper nanoparticles is 10μg / mL, it can show significant antibacterial properties compared with the control group. In addition, compared with the control group, the bacterial biomass showed a distinct purple color, and the mixed system containing core-shell carbon-coated copper nanoparticles had significantly less biomass adhering to the bottom of the well plate, indicating that the core-shell carbon-coated copper nanoparticle solution has good antibacterial properties as an antibacterial agent. With the increase of concentration, the antibacterial rate of core-shell carbon-coated copper nanoparticles is further improved.

[0050] Example 6

[0051] This example studies the antifungal properties of the aqueous solution of the core-shell carbon-coated copper nanoparticles prepared in Example 1. This example uses Aspergillus niger to verify the antifungal effect of its aqueous solution. The specific process is as follows:

[0052] (1) Use a Pasteur pipette to pipette 2 mL of PBS buffer into the activated cultured Aspergillus niger plate and gently shake to collect the Aspergillus niger spore liquid. The Aspergillus niger spore liquid without sample is used as the control group.

[0053] (2) The core-shell carbon-coated copper nanoparticles were prepared into suspensions of different concentrations (10, 20, 40 μg / mL) using PBS buffer, and then the spore solution of Aspergillus niger was mixed with PBS buffer and suspensions of core-shell carbon-coated copper nanoparticles of different concentrations at a volume ratio of 1:9. After the mixed system was cultured in a shaker at 37°C for 6 hours, 100 μL of the mixed solution was transferred to the plate culture medium, and the culture was kept at a constant temperature of 28°C in an incubator for 48 hours. The growth of Aspergillus niger on the plate was observed and photographed.

[0054] The implementation results are as follows Figure 7As shown, the growth of Aspergillus niger can be observed on the culture medium plates of the control group and the low concentration (20 μg / mL) core-shell carbon-coated copper nanoparticles as antibacterial agents. When the core-shell carbon-coated copper nanoparticles are used as antibacterial agents and their concentration is ≥20 μg / mL, the growth of Aspergillus niger is not observed on the culture medium plates, indicating that the core-shell carbon-coated copper nanoparticles also have excellent antifungal properties.

[0055] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the scope of the present invention.

Claims

1. A method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function, characterized in that: The steps include: using a plasma arc method to prepare, using pure copper as the anode, selecting a graphite rod as the cathode, and waiting for the vacuum degree of the arc furnace to reach 10 -4 Pa or above, the carbon source is injected into a high vacuum chamber, and after purification in argon, the black powder composed of nanoparticles is collected. The collected nanoparticles are subjected to a carbon shell burning process, and are recovered after cooling to obtain Cu@C.

2. The method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function according to claim 1, characterized in that: The carbon source is an organic compound composed of three elements, carbon, hydrogen and oxygen, or two elements, carbon and hydrogen.

3. The method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function according to claim 2, characterized in that: The carbon source is anhydrous ethanol or n-hexane.

4. The method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function according to claim 1, characterized in that: The Cu@C is a core-shell structure with copper as the core and porous carbon as the shell.

5. The method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function according to claim 1, characterized in that: The Cu@C has a spherical structure, a porous structure, a uniform size, and a particle size distribution between 30 and 100 nm.

6. The method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function according to claim 1, characterized in that: The carbon source is different, and the Cu@C shell thickness is different. When the carbon source is anhydrous ethanol, the carbon shell thickness of the prepared carbon-coated copper nanoparticles is between 8 and 10 nm; when the carbon source is cyclohexane, the carbon shell thickness of the prepared carbon-coated copper nanoparticles is between 10 and 19 nm.

7. The method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function according to claim 1, characterized in that: The carbon shell burning process temperature is 150-250°C.

8. The method for preparing a core-shell carbon-coated copper nano-antibacterial agent with sustained-release function according to claim 1, characterized in that: The carbon shell burning process has a heat preservation time of 0.5 to 3.0 hours.

9. A core-shell carbon-coated copper nano-antibacterial agent with sustained-release function, characterized in that: The carbon-coated copper nano-antibacterial agent is prepared by the preparation method according to any one of claims 1 to 8, and slowly releases copper element to kill Gram-positive bacteria, Gram-negative bacteria and fungi.

10. Use of the core-shell carbon-coated copper nano-antibacterial agent with sustained-release function as claimed in claim 9 in the preparation of medicines and / or bactericides for treating diseases caused by bacteria.

Citation Information

Patent Citations

  • Method of manufacturing nano-carbon packaged copper nano-particle and application of the same as heat conduction filling material

    CN101318220A

  • Application of copper nanomaterial with copper / carbon-core / shell structure in antibiosis

    CN102499260A

  • Preparation method and application of shell-core carbon-coated metal phosphide nanometer composite particle

    CN107317008A

  • Core-shell carbon nanofiber for hydrogen storage and process for preparing the fiber

    JP2003054901A

  • A method for fabricating of copper powder with carbon shell

    KR101269407B1

Cited By

  • Graphite / ferroferric oxide nano-particles with near-infrared photodynamic sterilization function, preparation method and application

    CN122536588A